Reproductivity And Validity Analysis Of Badminton Player Cognitive Performance Using Badminton Reaction Inhibition Test (BRIT) - Handayani Nila Praja; Rivo Panji Yudha; Sri Sundari; Wahyu Adhi Nugroho (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2020)
The purpose of this study was to analyze the reproducibility and validity of the Badminton Reaction Inhibition Test (BRIT) or the Badminton Reaction Barrier Test. BRIT measures four components: general-domain reaction time, badminton-specific reaction time, general-domain inhibition control, and badminton-specific inhibition control. Fifteen male national badminton athletes and nine non-national badminton players in Region 3 Cirebon participated in this study. Five participants were retested within three weeks on a specific badminton component. Reproducibility was acceptable for badminton specific reaction times (ICC = 0.626, CV = 6%) and for badminton specific inhibition controls (ICC = 0.317, CV = 13%). The validity of a good construct was shown in the specific poor reaction time that differentiated between national level athletes and non-national athletes (F = 6.650, p <0.05). National level athletes did not outperform non-national athletes on general-domain reaction times or on both inhibitory control components (p> 0.05). Concurrent validity for general-domain reaction times was good, as it was associated with the national rankings for national level athletes (? pro = 0.70, p <0.01) and non-national athletes (? = 0.70, p <0.05). ). No relationship was found between national ranking and badminton specific reaction time, nor between the two inhibition control components (p> 0.05). In conclusion, the reproducibility and validity of the control inhibition assessment are not confirmed, however, BRIT appears to be a valid and reproducible measure of reaction time in badminton players. Reaction times as measured by BRIT can provide input for training programs aimed at improving badminton player performance.